Optimal consumption and portfolio choice with loss aversion - Giuliano Curatola (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
This paper analyses the consumption-investment problem of a loss averse investor equipped with s-shaped utility over consumption relative to a time-varying reference level. Optimal consumption exceeds the reference level in good times and descend to the subsistence level in bad times. Accordingly, the optimal portfolio is dominated by a mean-variance component in good times and rebalanced more aggressively toward stocks in bad times. This consumption-investment strategy contrasts with customary portfolio theory and is consistent with several recent stylized facts about investors' behaviour. I also analyse the joint effect of loss aversion and persistence of the reference level on optimal choices. Finally, the strategy of the loss averse investor outperforms the conventional Merton-style strategies in bad times, but tend to be dominated by the conventional strategies in good times.
urn:nbn:de:hebis:30:3-395871
Keywords: G11; G12; 330; Loss-aversion; Habit-formation; Consumption-portfolio choice